Pengembangan Buku Ramah Cerna Berbasis Human Security sebagai Upaya Penguatan Profil Pelajar Pancasila di Sekolah Dasar - Sani Aryanto; Putri Ayuni Agustina; Meyke Erlianda; Anggraeni Eklecia Silaen; Ade Putri Puspitasari; Meliyanti (Elementary Teacher Education Program, Majalengka University, 2023)
The aim of this research is to provide a comprehensive overview of developing decodable books based on human security to strengthen the character profile of Pancasila students among students in the early reader category in elementary school. The research used Research and Development design through the ADDIE development model, including five steps, namely: analyze, design, development, implementation, and evaluation involving 6 teachers and 180 students from first grade in six elementary schools, including: (1) SDN Babelan Kota 9 Kota Bekasi; (2) SDN Teluk Pucung 3 Kota Bekasi; (3) SDN Bekasi Jaya 13 Kota Bekasi; (4) SDN Aren Jaya 15 Kota Bekasi; (5) SDN Aren Jaya 18 Kota Bekasi; and (6) SDN Teluk Pucung 6 Kota Bekasi. However, the results of this research are considered successful in developing decodable books that make it easier for teachers in the process of teaching early literacy and are categorized as very good with a percentage of 88%. This research produced six decodable books that are considered to have internalized the values of the Pancasila Student Profile and human security components. Therefore, this research will have implications for increasing the quantity and quality of decodable books that contain the values of the Pancasila Student Profile.